2003
DOI: 10.1046/j.1365-2303.2003.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology suggestive of glandular neoplasia: outcomes and suggested management

Abstract: Eighty-three cases having a cervical smear result showing abnormal glandular cells were identified and matched up with the diagnostic histology result. Thirty-four (41.0%) were associated with malignancy and 26 (31.3%) with a cervical intraepithelial lesion without invasion. Thirty-eight (45.8%) had conditions of the cervix as follows: 12 cases had invasive disease of the cervix; nine (10.8%) adenocarcinoma of cervix and three (3.6%) squamous carcinoma of cervix. Nineteen (22.9%) had cervical intraepithelial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
13
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
7
13
2
Order By: Relevance
“…Indeed, 33% of the patients with an endocervical AC and 56% with an endometrial AC were asymptomatic (Table 3). These observations are in contrast to the findings of Hare et al [29] who describe 28.3% asymptomatic patients with invasive endocervical AC diagnosed with the cytobrush technique. All of there 15 endometrial AC were symptomatic.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Indeed, 33% of the patients with an endocervical AC and 56% with an endometrial AC were asymptomatic (Table 3). These observations are in contrast to the findings of Hare et al [29] who describe 28.3% asymptomatic patients with invasive endocervical AC diagnosed with the cytobrush technique. All of there 15 endometrial AC were symptomatic.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study (Table 2) we found 261 'new' AGC-NOS cases diagnosed by cervico-vaginal cytology in our population, representing an AGC rate of 0.05% and increasing from 0.01% in 1990 to 0.09% in 1999. Other laboratories reported AGC rates ranging from 0.09% to 2.5% [8,18,20-22,27-29]. The reason why the prevalence of AGC in our series is considerably lower than that reported in other studies may be due to the exclusion of 25 cases with atypical ' epithelial ' cells at the beginning of the 1990's.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This feature of the disease poses another clinical problem, especially when the physician is confronted with an AGC Pap smear and an insufficient colposcopy. Many such women may have no cervical neoplasia, as reported previously (8)(9)(10) and corroborated in this sample. In this study, 26 (51%) out of 51 women with AGC were proven to have no clinically significant histologic lesion.…”
Section: Discussionsupporting
confidence: 90%
“…Most diagnoses of squamous and glandular cervical neoplasias are obtained with cervical cytology (Pap smears). Although squamous abnormalities in Pap smear strongly correlate with histopathologic squamous histologic findings, glandular abnormalities pose significant clinical problems because of their poor correlation with final histopathology (8–10) . The clinical significance of atypical glandular cells (AGC), an uncommon cytologic diagnosis defined in the last revision of the Bethesda System (2001), is still under debate.…”
mentioning
confidence: 99%